Optimization for the quick-code methods for the synthesis of discrete signals – physical carriers of data in information-communication systems: Fìz.-mat. model. ìnf. tehnol. 2021, 32:126-130 - Zamula, Alexander; Gorbenko, Ivan (PHYSICO-MATHEMATICAL MODELLING AND INFORMATIONAL TECHNOLOGIES, 2021)
The paper presents the theoretical foundations of synthesis and analysis of complex nonlinear discrete cryptographic signals, the basis for the synthesis of which are random (pseudo-random) processes, including algorithms for cryptographic transformation of information, as well as methods for optimizing the synthesis of these signals using decimation and discrete programming. namely, the method of branches and boundaries. In order to improve the performance of signal generation and processing, estimates of the effectiveness of the decimation procedure are proposed and presented. It is shown that the use of the studied signal systems will improve the efficiency of modern ICS (speed of data generation and processing devices, noise immunity, information security, secrecy, protection against input (imposition) of false messages, message falsification, data integrity, etc.). References Gorbenko, I. D., Zamula, А. А. (2017). “Cryptographic signals: requirements, methods of synthesis, properties, application in telecommunication systems”, Telecommunications and Radio Engineering, 76(12), 1079-1100, 2017. DOI doi.org/10.1615/telecomradeng.v76.i12.50 Gorbenko, I. D., Krasnobayev, V. A., Kuznetsov, A. A. (Eds.) (2020). ISCI’2020: Information Security in Critical Infrastructures. Collective monograph. Edited by . Ivan Gorbenko and Alexandr Zamula. Theoretical Basis of Synthesis of Complex Signal Quasiortogonal Systems. ASC Academic Publishing, USA. – ISBN: 978-1-7362833-0-1 (Hardback), ISBN: 978-1-7362833-1-8 (Ebook). Gorbenko, I. D., Zamula, O. A. (2017). Modeli ta metody syntezu kryptohrafichnykh syhnaliv ta yikh optymizatsiya za kryteriyem chasovoyi skladnosti. Matematychne ta kompʺyuterne modelyuvannya. Seriya: Fizyko-matematychni nauky: zb. Nauk. pratsʹ Instytut kibernetyky imeni V.M. Hlushkova Natsionalʹnoyi akademiyi nauk Ukrayiny, 15. DOI doi.org/10.15407/akademperiodyka.241.394 Gorbenko, I. D., Zamula, O. A., Lyk, Kh., Ch. (2020). Metody syntezu i formuvannya system neliniynykh dyskretnykh syhnaliv dlya suchasnykh informatsiyno-komunikatsiynykh system. Radiotekhnika: Vseukrayinsʹkyy mizhvidomchyy naukovo-tekhnichnyy zbirnyk, 126 – 132.